The Applications and the current status of silver nanoparticles in the field of Orthodontics - SUBRAMANIAN, ARAVIND KUMAR (The journal of contemporary issues in business and government, 2021)
Nanotechnology over past decades, has emerged as a mainstay in various fields and has been employed in various biomedical applications. It is currently being extensively used in the manufacture of drugs, as a diagnostic aid, in implants, as a prosthetic material and in tissue engineering. With the recent introduction of advanced Nano robotic models in local anesthetic procedures, the applications and importance of nanotechnology in the field of healthcare have gained renewed impetus. This review primarily throws light on the current applications of silver nanoparticles in the field of Dentistry, emphasizing on orthodontics in particular, with regard to their antimicrobial properties, anti-cariogenic effects, Nano silver coating applications of orthodontic brackets, micro implants, biocompatibility analysis and fixed orthodontic appliances.